2018
DOI: 10.1080/01621459.2017.1356319
|View full text |Cite
|
Sign up to set email alerts
|

Linear Hypothesis Testing in Dense High-Dimensional Linear Models

Abstract: We propose a methodology for testing linear hypothesis in high-dimensional linear models. The proposed test does not impose any restriction on the size of the model, i.e. model sparsity or the loading vector representing the hypothesis. Providing asymptotically valid methods for testing general linear functions of the regression parameters in high-dimensions is extremely challenging -- especially without making restrictive or unverifiable assumptions on the number of non-zero elements. We propose to test the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 56 publications
(132 reference statements)
1
52
0
Order By: Relevance
“…To our knowledge, this was the first result for √ n-consistent inference about dense contrasts of β c at the time that we first circulated our manuscript. We note, however, simultaneous and independent work by Zhu and Bradic (2016), who developed a promising method for testing hypotheses of the form ξβ c = 0 for potentially dense vectors ξ; their approach uses an orthogonal moments construction that relies on regressing ξX i against a .p − 1/-dimensional design that captures the components of X i orthogonal to ξ.…”
Section: Approximate Residual Balancing As Debiased Linear Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this was the first result for √ n-consistent inference about dense contrasts of β c at the time that we first circulated our manuscript. We note, however, simultaneous and independent work by Zhu and Bradic (2016), who developed a promising method for testing hypotheses of the form ξβ c = 0 for potentially dense vectors ξ; their approach uses an orthogonal moments construction that relies on regressing ξX i against a .p − 1/-dimensional design that captures the components of X i orthogonal to ξ.…”
Section: Approximate Residual Balancing As Debiased Linear Estimationmentioning
confidence: 99%
“…(There are, of course, some exceptions to this assumption. In recent work, Javanmard and Montanari (2015) showed that inference of β c is possible even when k n log.p/ in a setting where X is a random Gaussian matrix with either a known or extremely sparse population precision matrix; Wager et al (2016) showed that lasso regression adjustments allow for efficient average treatment effect estimation in randomized trials even when k n log.p/, whereas the method of Zhu and Bradic (2016) for estimating dense contrasts ξβ c does not rely on sparsity of β c and instead places assumptions on the joint distribution of ξX i and the individual regressors. The point in common between these results is that they let us weaken the sparsity requirements at the expense of strengthening our assumptions about the X-distribution.…”
Section: Debiasing Dense Contrastsmentioning
confidence: 99%
“…The sensitivity of our procedure to the choice of the tuning parameters is given in Table 4. Similarly to Zhu and Bradic (2016), we chooseη γ = 0.05 V P V /n.…”
Section: Tuning Parametersmentioning
confidence: 99%
“…Nominal level is taken to be 5%. LM procedure consists in applying the linear model procedure of Zhu and Bradic (2016) to the mixed model while MM procedure consists in applying our mixed model procedure. Parameters are n = 200, p = 500, N = 50, s = 5.…”
Section: Gaussian Mixed Modelmentioning
confidence: 99%
“…[18] consider construction of confidence sets for dense functionals given by a(β) = β l for various 1 l ∞. Perhaps the most closely related current papers are [58] and [59]. Both [58] and [59] construct hypothesis tests for objects similar to those considered in our paper via 1 -projections of coefficient estimates to the set of coefficients consistent with the null.…”
Section: Introductionmentioning
confidence: 99%